Sosialisasi Dakwah Sebagai Proses Komunikasi: Efektivitas Dakwah Digital Sebagai Proses Komunikasi Interaktif di Kalangan Gen Z - Edi Sumardi; Harkat Aulia Harbi; Misnan Jaelani; Muh Zazin (Lembaga Pengembangan Kinerja Dosen, 2025)
The rapid development of information technology has triggered significant changes in communication patterns, including in da'wah activities. Amidst digital dominance and the rapid flow of information, a da'wah approach relevant to the communication characteristics of Gen Z is crucial. Gen Z is known for its fast, interactive communication style and preference for digital media. Therefore, this community service program is designed to introduce da'wah as an effective two-way communication process in addressing these dynamics. The main objective of this program is to improve digital da'wah literacy and foster motivation and practical skills in creatively conveying Islamic messages through social media platforms. This community service activity is carried out through a series of activities, including outreach, interactive discussions, and practical simulations for creating digital da'wah content. The outreach is intended to provide a basic understanding of da'wah in a digital context. Interactive discussions allow participants to share views and understand how da'wah can be carried out effectively in cyberspace. Meanwhile, the da'wah content creation practice provides participants with the opportunity to directly engage in creating da'wah messages that can be disseminated through social media. Evaluation of the activity is carried out through pre- and post-tests held before and after the program implementation. The analysis results showed an increase in participants' understanding of more than 35% across all tested indicators. The highest increase (56.3%) was recorded in their understanding of the importance of two-way communication in da'wah. Previously, many participants considered da'wah to be an activity limited to religious leaders. However, after participating in this program, they began to understand that da'wah is a task for every individual, and can be carried out through media closely related to their daily lives. Overall, this program succeeded in increasing knowledge, critical awareness, and enthusiasm for contextual da'wah among Gen Z.